Association between cancer and cardiovascular disease risk: a cross-sectional study of 241,064 individuals - Zhu, Lianmin; Zhou, Wenqing; Yang, Yukang; Rao, Huan; Liu, Yizhi; Rao, Yunwei (Frontiers in Oncology, 2026)
BackgroundAdvances in cancer therapy have improved survival, yielding a larger population of cancer survivors, with cardiovascular disease (CVD) becoming a major chronic health issue among them. However, the association between cancer and CVD risk remains unclear.MethodsThis study conducted a cross-sectional analysis utilizing 2023 United States Behavioral Risk Factor Surveillance System (BRFSS) data. Propensity score matching (PSM) balanced the observed covariates between the cancer and non-cancer groups. Univariate and multivariate logistic regression were employed to examine the relationship between cancer history and CVD. Subgroup analyses evaluated this association across different populations. Finally, univariate and multivariate logistic regression identified CVD risk factors among cancer survivors.ResultsBefore PSM, CVD prevalence was 20.7% in cancer patients, significantly higher than 10.7% in non-cancer individuals. Multivariate logistic regression revealed that cancer remains positively associated with CVD risk even after adjusting covariates (OR = 1.16, 95% CI: 1.12-1.20, P < 0.001). Analysis after 1:2 PSM further validated this association: The prevalence of CVD was higher in the cancer group than in the matched control group (20.7% vs. 18.2%; OR = 1.14, 95% CI: 1.10–1.18, P < 0.001). Except for diabetes and chronic kidney disease (CKD) subgroups, most subgroups of cancer are positively associated with CVD risk (OR > 1, P < 0.05). Among cancer survivors, advanced age, comorbidities (hypertension, diabetes, CKD), depression, and smoking were significantly positively associated with CVD risk, while female sex, aerobic physical activity, and higher income were significantly negatively associated with cardiovascular disease risk.ConclusionThere is a significant positive correlation between cancer and CVD risk, indicating that CVD risk assessment and prevention efforts for cancer survivors should be strengthened.